Variable content and distribution of arabinogalactan proteins in banana (Musa spp.) under low temperature stress - Yan, Yonglian; Takáč, Tomáš; Li, Xiaoquan; Chen, Houbin; Wang, Yingying; Xu, Enfeng; Xie, Ling; Su, Zhaohua; Šamaj, Jozef; Xu, Chunxiang (Frontiers in Plant Science, 2015)
Information on the spatial distribution of arabinogalactan proteins (AGPs) in plant organs and tissues during plant reactions to low temperature (LT) stresses is limited. In this study, the extracellular distribution of AGPs in banana leaves and roots, and their changes under LT stresses were investigated in two genotypes differing in chilling tolerance, by immuno-techniques using 17 monoclonal antibodies against different AGP epitopes. Changes in total classical AGPs in banana leaves were also tested. The results showed that AGP epitopes recognized by JIM4, JIM14, JIM16 and CCRC-M32 antibodies were primarily distributed in leaf veins, while those recognized by JIM8, JIM13, JIM15 and PN16.4B4 antibodies exhibited predominant sclerenchymal localization. Epitopes recognized by LM2, LM14 and MAC207 antibodies were distributed in both epidermal and mesophyll cells. Both genotypes accumulated classical AGPs in leaves under LT treatment, and the chilling tolerant genotype contained higher classical AGPs at each temperature treatment. In addition, the abundance of JIM4 and JIM16 epitopes in the chilling-sensitive genotype decreased slightly after LT treatment, and this trend was opposite for the tolerant one. LT induced accumulation of LM2- and LM14-immunoreactive AGPs in the tolerant genotype compared to the sensitive one, especially in phloem and mesophyll cells. These epitopes thus might play important roles in banana LT tolerance. Different AGP components also showed differential distribution patterns in banana roots. In general, banana roots started to accumulate AGPs under LT treatment earlier than leaves. The levels of AGPs recognized by MAC207 and JIM13 antibodies in the control roots of the tolerant genotype were higher than in the chilling sensitive one. Furthermore, the chilling tolerant genotype showed high immuno-reactivity against JIM13 antibody. These results indicate that several AGPs are likely involved in banana tolerance to chilling injury.